Effects of diffusion on composite materials' properties - Liu, Wan Qing (2015)
Today, Fibre-Reinforced Polymer (FRP) has gained popularity in many applications due to its light weight and high strength. This project investigates the effect of seawater on the properties of FRP material to study the suitability of the material in marine application. This project investigates the material system of Hexforce 1581 plain woven glass fibre/ Hexply F655 Bismaleimide (BMI). Water diffusion test was done on the specimens by soaking them in artificial water of 3.5% salt concentration and at 50℃. The diffusion coefficient and water absorption curve were obtained from the water diffusion test. Fatigue tests were done on the specimens at three time periods specifically at zero soaking hour (dry specimen), 1700 soaking hours and 2700 soaking hours. The results from the fatigue tests were used to analyse the effects of seawater environment on the material by comparing the S-N curves and stiffness degradation curves. From the water diffusion test, the diffusion coefficient was worked out to be 3.3×〖10〗^(-7) 〖mm〗^2/s and the water diffusion curve obtained followed Fickian’s law. Some general trends were observed from the fatigue tests. Firstly, from the S-N curves, the wet specimens have longer lifetime than the dry specimens. One possible reason for this result is due to the enhancement of ductility of the wet specimens which increases the fatigue life of the wet specimens [1]. Secondly, another set of trends can be seen from the stiffness degradation curves. When stress level increases, both the initial and final stiffness decrease. Also, it was observed that the initial and final stiffness of the specimens increases with longer exposure to the artificial seawater. However, these trends are not always true for every test conditions due to experimental errors and the inconsistency in the material’s behaviour at different test conditions. Finally, a stiffness degradation model was proposed using the experimental data.